2016
DOI: 10.1051/0004-6361/201527323
|View full text |Cite
|
Sign up to set email alerts
|

The GTC exoplanet transit spectroscopy survey

Abstract: We observed the hot Jupiter HAT-P-32b (also known as HAT-P-32Ab) to determine its optical transmission spectrum by measuring the wavelength-dependent planet-to-star radius ratios in the region between 518 -918 nm. We used the OSIRIS instrument at the GTC in long slit spectroscopy mode, placing HAT-P-32 and a reference star in the same slit and obtaining a time series of spectra covering two transit events. Using the best quality data set, we were able to yield 20 narrow-band transit light curves, with each pas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
11
37
0
Order By: Relevance
“…Previous ground-based observations of the transit of HAT-P-32b in the optical wavelengths (Gibson et al 2013;Zhao et al 2014;Mallonn & Strassmeier 2016;Nortmann et al 2016) did not find evidence of spectral modulations due to molecules. Our cloud top pressure is consistent with their measurements within 1σ, hence the water detection in the infrared is not controversial.…”
Section: Comparison With Other Observationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous ground-based observations of the transit of HAT-P-32b in the optical wavelengths (Gibson et al 2013;Zhao et al 2014;Mallonn & Strassmeier 2016;Nortmann et al 2016) did not find evidence of spectral modulations due to molecules. Our cloud top pressure is consistent with their measurements within 1σ, hence the water detection in the infrared is not controversial.…”
Section: Comparison With Other Observationsmentioning
confidence: 66%
“…HAT-P-32b is one of the most inflated exoplanets discovered, being less massive than Jupiter (M M 0.79 p J u p = ) but having almost twice its radius (R R 1.789 p J u p = ). The atmosphere of HAT-P-32b has been observed with ground-based instruments in the optical wavelengths, revealing a featureless transmission spectrum (Gibson et al 2013;Zhao et al 2014;Mallonn & Strassmeier 2016;Nortmann et al 2016). In addition, Zhao et al (2014) suggested the presence of a thermal inversion in the atmosphere of HAT-P-32bto interpret eclipse observations.…”
Section: Introductionmentioning
confidence: 99%
“…As in Nortmann et al (2016), the Bayesian Information Criterion (BIC) was used to select the best light curve model. The BIC penalizes a high χ 2 value and/or the number of free parameters used in the fitting procedure; the model that presents the lowest BIC is the one selected.…”
Section: Model Selectionmentioning
confidence: 99%
“…All the tested models present a synthetic transit model with a time dependency to reproduce a second-order color effect not corrected by the differential photometry, and a FWHM dependent polynomial to model the systematic effects produced by seeing variations. The FWHM correction was introduced because seeing variations affected the number of pixels in which the major part of the stellar flux is contained, and this pixel-dependent effect will act as a systematic correlated with FWHM (see Nortmann et al 2016;Chen et al 2017). With a slit 40 arcsec in width, the flux losses produced by not being able to measure the flux contained in the wings of the spectral profile are negligible.…”
Section: Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation